Selina, Countess of Huntingdon - Harding, Alan (Epworth, 2007)
The Countess of Huntingdon's Connexion is one of the most interesting phenomena in the history of Non-Conformity and one of the most neglected strands in the history of the Evangelical Revival. Alan Harding here explores its links with Methodism and paints a picture of a small but significant denomination.
Includes bibliographical references (p. 206-209) and index
Keywords: Huntingdon, Selina Hastings / Countess of / 1707-1791; Huntingdon, Selina Hastings <Countess of, 1707-1791>; Huntingdon, Selina Hastings of -- 1707-1791; Countess of Huntingdon's Connexion; Countess of Huntingdon's Connexion -- History; Geschichte 1700-1800; Geschichte 1730-1800; Geschichte; Kirchengeschichte; Calvinistic Methodists -- England -- Biography; Evangelikale Bewegung; England / Church history / 18th century; England -- Church history -- 18th century; Großbritannien; Biografie